2015
DOI: 10.1186/s12944-015-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetrapleura tetraptera spice attenuates high-carbohydrate, high-fat diet-induced obese and type 2 diabetic rats with metabolic syndrome features

Abstract: BackgroundTetrapleura tetraptera, a seasoning and nutritive spice is also used in western African folk medicine in the management of wide variety of diseases including diabetes, inflammation and hypertension. Flavonoids and saponins are some abundant secondary metabolic constituents in the fruits of this plant. This study aimed at evaluating the potential therapeutic action of the polyphenol-rich hydroethanolic extract (HET) of this fruit in experimentally induced obese and type 2 diabetic rats (T2DM) with cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 59 publications
8
43
0
Order By: Relevance
“…The vildagliptin treatment significantly modulated these parameters and showed its antioxidant activity. Our data are in accordance with the previous report by Renna NF et al and Kuate et al 13,17 …”
Section: Mechanism; Dpp-iv Pathway Inflammatory Oxidant Variablessupporting
confidence: 94%
See 2 more Smart Citations
“…The vildagliptin treatment significantly modulated these parameters and showed its antioxidant activity. Our data are in accordance with the previous report by Renna NF et al and Kuate et al 13,17 …”
Section: Mechanism; Dpp-iv Pathway Inflammatory Oxidant Variablessupporting
confidence: 94%
“…Study by Kuate D et al supported our finding. 13 The C-peptide determined by Nora M. El-Sheikh showed reduced level of C-peptide in diabetic rats similar to present study which is restored by treatment with vildagliptin.…”
Section: Diabetessupporting
confidence: 88%
See 1 more Smart Citation
“…Hydrogenated vegetable fat used in our study promoted an increase in serum triacylglycerol and total cholesterol levels. Long term intake of TFAs altered plasma lipoprotein profile that increased the risk of cardiovascular diseases, decreased insulin sensitivity, and higher risk of type 2 diabetes (Ibrahim et al, 2005;Lichtenstein et al, 2001). Based on our knowledge this study was the first study revealed metabolic syndrome features with the use of fat sources that mimic daily consumed fat in human.…”
Section: Development Of Dyslipidemiamentioning
confidence: 84%
“…Moreover, the blood glucose of HFHS group was significantly higher than that of NC group at the end of study. As explained by (Kuate et al, 2015), high carbohydrate and fat diet only would not induce frank hyperglycemia. Moreover, (Wang et al, 2007) revealed that hyperglycemia appeared at 3-4 weeks subsequent to streptozotocin administration.…”
Section: Development Of Hyperglycemiamentioning
confidence: 95%